Health Seeking Behaviour and Practices on Immunization for under Five Years Children after Ebola Virus Disease Outbreak. A Case Study in Margibi County-Liberia - Dovillie, N.K (University of Ghana, 2016)
Introduction Epidemics can be lethal and if not approached appropriately, it may take away many lives and even disrupt the stability of a nation. In most cases, Children (0 - 59months) are found to be one of the most susceptible populations. In Africa, childhood immunization remains a critical health service. Outbreak of the Ebola virus disease led to collapse of health services including immunization services. Hence, this study seeks to investigate factors influencing health seeking behaviour for childhood immunization in post Ebola virus disease outbreak in Margibi County. Methodology A cross-sectional design using quantitative approach was used. A total of 400 respondents were enrolled and interviewed in this study. Systematic randomized sampling technique was used in the selection of participants. For the data analyses process, StataMP 13 software was used for the descriptive and statistical analyses. Results Findings from this study show that the Ebola virus disease outbreak adversely affected parents' behaviour towards accessing immunization services for wards. The fear for Ebola vaccine and closure at health facilities were the leading influencing factors for less access of immunization for children under five in post Ebola Margibi County. Fear for Ebola vaccine [OR=1.96 (95%CI= 0.968-3.972), p=0.05] accounted for 75.23% of all reasons for vaccine refusal. Participants' knowledge on immunization was found to be high (90.53%). Parents and caregivers with higher education were 2.02 times more likely to vaccinate their child/children compared to those with no education. Education was significantly correlated to accessing vaccination after Ebola outbreak [AOR= 2.33, (95%CI=1.335-4.071), p <0.05] Conclusion: Ebola virus disease outbreak posed several challenges to childhood immunization services. Fear and low educational status adversely influence parent's healthy behaviour for childhood immunization services after Ebola disease outbreak. In order to reduce fear for immunization in post Ebola outbreaks, health authorities must timely, regularly, and accurately disseminate information through trusted medium for public consumption.
Thesis (MSc) -University of Ghana, 2016
Keywords: Health Seeking Behaviour; Immunization; Ebola Virus; Margibi County-Liberia